Whole-Genome Sequences of Mycobacterium abscessus subsp. massiliense Isolates from Brazil - Machado, Edson (2021)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Genética Molecular de Microrganismos. Rio de Janeiro, RJ, Brasil.